Ratiometric theranostic nanoprobe for pH imaging-guided photodynamic therapy. Issue 18 (25th April 2019) - Cheng, Hong; Fan, Gui-Ling; Fan, Jing-Hao; Zhao, Lin-Ping; Zheng, Rong-Rong; Yu, Xi-Yong; Li, Shi-Ying
Abstract : A FRET-based theranostic nanoprobe is fabricated for ratiometric pH imaging-guided photodynamic therapy against tumor cells. Abstract : An abnormal pH microenvironment results from the development of tumors, and also affects the therapeutic efficiency of anti-tumor drugs. In this work, a Förster resonance energy transfer (FRET)-based theranostic fluorescent nanoprobe was constructed for simultaneous ratiometric pH sensing and tumor-targeted photodynamic therapy. Based on the FRET process between rhodamine B and protoporphyrin IX (PpIX), the fabricated nanoprobe exhibited excellent pH responsiveness in both solutions and live cells with the ratiometric fluorescence changes. Moreover, this ratiometric pH fluorescent nanoprobe also possessed the capability for pH-responsive singlet oxygen ( 1 O2 ) generation under light irradiation, guiding robust photodynamic therapy in a pH-dependent manner. Benefiting from the enhanced permeability and retention (EPR) effect, the nanoprobe could significantly inhibit tumor growth and metastasis via targeted photodynamic therapy in vivo . This work presents a novel paradigm for precise tumor theranostics by ratiometric pH fluorescence imaging-guided photodynamic therapy.